Interaction with the CCT chaperonin complex limits APOBEC3A cytidine deaminase cytotoxicity. (4th August 2021) - Green, Abby M; DeWeerd, Rachel A; O'Leary, David R; Hansen, Ava R; Hayer, Katharina E; Kulej, Katarzyna; Dineen, Ariel S; Szeto, Julia H; Garcia, Benjamin A; Weitzman, Matthew D
Abstract: The APOBEC3 cytidine deaminases are implicated as the cause of a prevalent somatic mutation pattern found in cancer genomes. The APOBEC3 enzymes act as viral restriction factors by mutating viral genomes. Mutation of the cellular genome is presumed to be an off‐target activity of the enzymes, although the regulatory measures for APOBEC3 expression and activity remain undefined. It is therefore difficult to predict circumstances that enable APOBEC3 interaction with cellular DNA that leads to mutagenesis. The APOBEC3A (A3A) enzyme is the most potent deaminase of the family. Using proteomics, we evaluate protein interactors of A3A to identify potential regulators. We find that A3A interacts with the chaperonin‐containing TCP‐1 (CCT) complex, a cellular machine that assists in protein folding and function. Importantly, depletion of CCT results in A3A‐induced DNA damage and cytotoxicity. Evaluation of cancer genomes demonstrates an enrichment of A3A mutational signatures in cancers with silencing mutations in CCT subunit genes. Together, these data suggest that the CCT complex interacts with A3A, and that disruption of CCT function results in increased A3A mutational activity. Synopsis: The CCT chaperonin complex interacts with the cytidine deaminase APOBEC3A that causes genotoxicity when dysregulated. Depletion of CCT leads to APOBEC3A‐induced DNA damage and cytotoxicity, implicating the CCT complex as a regulator of APOBEC3A activity. The CCT chaperonin complex interacts with the APOBEC3A cytidine deaminase. Depletion of CCT complex components results in increased DNA damage and cytotoxicity by APOBEC3A. Mutations in CCT genes in human tumors are correlated with an increased APOBEC3‐associated mutational burden. The CCT complex acts as a regulator of APOBEC3A‐mediated genotoxicity. Abstract : The CCT chaperonin complex interacts with the cytidine deaminase APOBEC3A that causes genotoxicity when dysregulated. Depletion of CCT leads to APOBEC3A‐induced DNA damage and cytotoxicity, implicating the CCT complex as a regulator of APOBEC3A activity.